A Genealogycal Study of Islamic Education Science at the Faculty of Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga - Suyadi, Suyadi; Sutrisno, Sutrisno (Al-Jami'ah Research Centre, 2018)
This study traces the genealogy of Islamic education at the Faculty of Ilmu Tarbiyah dan Keguruan (FITK) Sunan Kalijaga State Islamic University Yogyakarta. The genealogycal approach used in Foucault’s terminology means that the objectivity of science covers two aspects, namely the archeology of knowledge and power. Data is comprised of ideas and opinions that develop among lecturers at FITK. Data is analyized interpretatively, descriptively, and comparatively. Findings show that in the early period of its formation (1951), Islamic education science at FITK was influenced by religious teachings brought from the Middle East. But since the secularization of Islamic education in Turkey led by Fethullah Gülen (1990), the mecca of Islamic education has split into two poles; on the one side, it follows dogmatic religious teachings stemming from Middle East traditions, and on the other side, it needs to respond to the Western secular tradition. Since 2007 the dynamics of FITK has moved toward a dialectics of integrative Islamic education.[Tujuan penelitian ini adalah melacak akar genealogi integrasi keilmuan pendidikan Islam di Fakultas Ilmu Tarbiyah dan Keguruan (FITK) Universitas Islam Negeri Sunan Kalijaga. Pendekatan genealogi dalam terminologi Foucault dimaksudkan bahwa obyektivitas ilmu mencakup dua unsur, yakni arkeologi pengetahuan dan kekuasaan. Data-data berupa ide dan gagasan yang lahir dan berkembang dari para dosen FITK dianalisis secara interpretatif, deskriptif dan komparatif. Hasil penelitian menunjukkan bahwa pada awal berdirinya (1951), embrio keilmuan pendidikan Islam di FITK dikuasai ilmu-ilmu agama dari Timur Tengah. Tetapi, sejak terjadi sekularisasi pendidikan Islam di Turki yang dipimpin Fethullah Gülen (1990), kiblat keilmuan pendidikan Islam terpecah dan dikotomi; di satu sisi harus tunduk pada kebenaran ilmu-ilmu agama dari Timur Tengah tetapi di sisi lain harus merespon ilmu pendidikan sekuler dari Barat. Dalam perkembangan mutakhir, tepatnya sejak 2007 dinamika keilmuan FITK bergerak menuju dialektika keilmuan pendidikan Islam yang integratif]Keywords: IntegratedIslamic Education, scientific genealogy, the Faculty of Tarbiyah and Teaching.